Impact of surgical specialization on long-term survival after emergent colon cancer resections - Engdahl, Jenny; Öberg, Astrid; Bech-Larsen, Sandra; Öberg, Stefan (Scandinavian Journal of Surgery, 2025)
Background: The impact of surgical specialization on long-term survival in patients undergoing emergent colon cancer resections remains unclear. Method: A retrospective analysis was conducted on all patients who underwent emergent colon cancer resections at a secondary care hospital between 2010 and 2020. The most senior surgeon performing the procedures was classified as colorectal surgeon (CS) or non-colorectal surgeon (NCS). NCS was further divided into acute care surgeons (ACSs) or general surgeons (GSs). Overall survival (OS) and cancer-free survival (CFS) were compared in patients operated by surgeons with different specializations. Results: A total of 235 emergent resections were performed during the study period, of which 99 (42%) were performed by CS and 136 (58%) by NCS. In adjusted Cox regression analyses, OS and CFS were similar in patients operated on by CS and NCS (hazard ratio (HR) for OS: 1.02 (0.72–1.496), p = 0.899 and HR for CFS: 0.91 (0.61–1.397), p = 0.660). Similarly, OS and CFS were equivalent in patients operated by ACS and CS (HR for OS: 1.10 (0.75–1.62), p = 0.629 and HR for CFS: 1.24 (0.80–1.92), p = 0.343). However, patients operated by GS had significantly shorter OS and CFS (HR for OS: 1.78 (1.05–3.00), p = 0.031 and HR for CFS: 1.83 (1.02–3.26), p = 0.041) compared with those operated by ACS and CS. Conclusion: Long-term survival after emergent colon cancer resections was similar in patients operated on by CS and NCS, and the subgroup of ACS, indicating equivalent comparable surgical quality. The less favorable poorer survival observed for patients operated on by GS may possibly be due to less frequent exposure to colorectal and emergent surgery.
Publisher Copyright: © The Finnish Surgical Society 2025. This article is distributed under the terms of the Creative Commons Attribution 4.0 License (https://creativecommons.org/licenses/by/4.0/) which permits any use, reproduction and distribution of the work without further permission provided the original work is attributed as specified on the SAGE and Open Access pages (https://us.sagepub.com/en-us/nam/open-access-at-sage).
Keywords: cancer-free survival; colon cancer; emergency colon resection; Long-term outcome; overall survival; surgeon specialization